The Adult Ts65Dn Mouse Model of Down Syndrome Shows Altered Swallow Function - Glass, Tiffany J.; Valmadrid, Luke Carmichael V.; Connor, Nadine P. (Frontiers in Neuroscience, 2019)
There are increased risks for deglutition disorders in people with Down Syndrome (DS). Although mouse models have been used to study the biological underpinnings of DS in other areas, relatively little is known about swallowing phenotypes in these models. We hypothesized that swallowing performance would be affected in adult mouse models of DS, relative to typical control mice. Videofluoroscopic swallow studies (VFSS) were conducted on adults of two mouse models of DS: Ts65Dn and Dp(16)1Yey, and evaluated in comparison with age-matched controls. Relative to other groups, adult Ts65Dn showed significantly slower swallow rates, longer inter-swallow intervals (ISI), and greater numbers of jaw excursion cycles preceding each swallow. In contrast, adult Dp(16)1Yey mice showed swallowing performance similar to control mice. Exploratory quantitative analyses of the intrinsic tongue (transverse muscle), and extrinsic tongue muscles (genioglossus, styloglossus, hyoglossus) showed no significant differences between genotype groups in myosin heavy chain isoform profiles. Collectively, these findings suggest that while swallowing is typical in adult Dp(16)1Yey, swallowing in adult Ts65Dn is atypical due to unknown causes. The finding that adult Ts65Dn may have utility as a model of dysphagia provides new opportunities to elucidate biological underpinnings of dysphagia associated with DS.